AN ANALYSIS OF SPEAKING ANXIETY AND AFFECTIVE LANGUAGE LEARNING AMONG STUDENTS OF ENGLISH LITERATURE IN MEDAN - Ginting, Hestika; Sebayang, F Ari Anggraini (Fakultas Ilmu Pendidikan Universitas Sari Mutiara Indonesia, 2021)
This study examines the speaking anxiety level and the employment of affective language learning strategies among English Applied Linguistics students in Medan, including the relationship between the two aforementioned variables. The research data were collected by administering a set of questionnaire encompassing 11 items assessing the comprehension apprehension factor and 6 items assessing fear of negative evaluation factor which were adopted from Foreign Language Classroom Anxiety Scales and also 6 items assessing the affective language strategies. There were 60 students of English Applied Linguistics participated in the study, comprising of 16 male students and 44 female students. This study found that the level of the speaking anxiety of the respondents was generally moderate, with the level of comprehension apprehension factor and the fear of evaluation were also moderate. The results suggest that the respondents in the present study moderately employed the affective language learning strategies in English medium classes. This study also found that students’ speaking anxiety level is negatively correlated with the involvement of affective language learning strategies in the process of language learning.